2013
DOI: 10.1111/tpj.12229
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide transcript analysis of early maize leaf development reveals gene cohorts associated with the differentiation of C4 Kranz anatomy

Abstract: Summary Photosynthesis underpins the viability of most ecosystems, with C4 plants that exhibit ‘Kranz’ anatomy being the most efficient primary producers. Kranz anatomy is characterized by closely spaced veins that are encircled by two morphologically distinct photosynthetic cell types. Although Kranz anatomy evolved multiple times, the underlying genetic mechanisms remain largely elusive, with only the maize scarecrow gene so far implicated in Kranz patterning. To provide a broader insight into the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
152
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(154 citation statements)
references
References 101 publications
(113 reference statements)
2
152
0
Order By: Relevance
“…Although analyses of transcriptional variation during maize leaf development have provided us with new insights, all these studies were restricted to one genetic background (Li et al, 2010;Pick et al, 2011;Liu et al, 2013b;Wang et al, 2013Wang et al, , 2014Yu et al, 2015). Adding an additional layer of information, phenotypic variation in mapping populations, and combining this with transcriptome variation in these populations offers new opportunities to identify genes and regulatory mechanisms that are at the basis of phenotypic differences (Andorf et al, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although analyses of transcriptional variation during maize leaf development have provided us with new insights, all these studies were restricted to one genetic background (Li et al, 2010;Pick et al, 2011;Liu et al, 2013b;Wang et al, 2013Wang et al, , 2014Yu et al, 2015). Adding an additional layer of information, phenotypic variation in mapping populations, and combining this with transcriptome variation in these populations offers new opportunities to identify genes and regulatory mechanisms that are at the basis of phenotypic differences (Andorf et al, 2012).…”
mentioning
confidence: 99%
“…Transcriptional dynamics during early development of embryonic leaves were surveyed by Liu et al (2013b) and Yu et al (2015). Additionally, the regulatory and functional differentiation of various leaf cell types was examined by transcriptome analysis (Li et al, 2010;Wang et al, 2013Wang et al, , 2014. The transcriptional variation between tissue types and cell types during development (Li et al, 2010;Wang et al, 2013Wang et al, , 2014 illustrates the importance of focusing the analysis of a given process on those tissues where the process takes place.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This set of data provided a global picture of the transcriptional dynamics of genes for early leaf development during maize seed germination and shed light on the succession of biological processes during this period. Wang et al (7) investigated the transcriptomes of Kranz (i.e., the foliar leaf blade) and non-Kranz (the husk leaf sheath) maize leaves to identify cohorts of genes associated with procambium initiation and vascular patterning. Recently, Wang et al (8) conducted comparative transcriptomic and metabolomic analyses of developing leaves in maize and rice and identified putative structural and regulatory components important for C4 and C3 photosynthesis.…”
mentioning
confidence: 99%
“…Recent work has shown that the SCARECROW (SCR) gene that is responsible for vein formation in roots, can produce proliferated bundle sheath cells as well as other changes that can be coupled to the shift to the Kranz anatomy (Slewinski et al, 2012). Further work supports this relation by describing the role that the upstream interacting partner of SCR, SHORT-ROOT (SHR) plays in the variations in anatomy seen in various C4 species (Wang et al, 2013;Slewinski et al, 2014).…”
Section: Introductionmentioning
confidence: 59%